Şii Siyasi Düşüncesi Bağlamında İran İslam Cumhuriyeti Anayasası'nda Otoritenin Kaynağı - (:unkn) unknown (My University, 2007)
İran İslam Cumhuriyeti Anayasası, hem otoritenin kaynağı hem de modern dönemde teokratik bir devletin imkânı etrafındaki tartışmalar bakımından önemli bir metindir. Anayasa’nın temelini oluşturan velâyet-i fakîh doktrini, fakîhe (rehber) devletin bütün organlarına hükmetme yetkisi vermektedir; çünkü veli-yi fakîh, Allah’ın on ikinci (gâib) imama verdiği mutlak siyasi otoritenin günümüzdeki yegane temsilcisidir. Bu yüzden merkezini velâyet-i fakîh anlayışının oluşturduğu İran İslam Cumhuriyeti’nde dinî-dünyevî şeklinde bir ayrıma gitmek olası değildir. Onikinci İmam’ın siyasi velayetini temsil eden fakîh, sonuçta gâib imam ve Allah adına hareket etmektedir. Dolayısıyla onun devlet ve toplum idaresine ilişkin vermiş olduğu hükümler, vatandaşların yanı sıra ictihâd hürriyetine sahip olan Şii ulema için de bağlayıcılığı olan bir husustur. Bu yüzden, velâyet-i fakîh makamını işgal eden rehbere itaatin vacip olup ona itirazın dinsizlik olduğu bile ileri sürülebilmiştir. Halkın doğrudan veli-yi fakîh’in seçimine katılmasının engellenip millet iradesinin göz ardı edildiği bir sistemde, atanmışlarla seçilmişler arasındaki kriz atanmışlar lehine sonuçlanmıştır. Seçilmişler de, Humeyni’nin ortaya koyduğu çizgiye (hatt-ı imâm) sadık kaldıkları sürece sistem tarafından meşru kabul edilmişlerdir.

The Constitution of the Islamic Republic of Iran is an important text both in terms of discussing the possibility of a theocratic state in the modern era and as the main source of the authority. The velâyat-i fakîh doctrine which forms the basis of the Constitution gives the fakih (guide) authority to govern all organs of the state. This is because the veli-yi fakîh is considered to be the sole representative of the absolute political authority given to the 12th Imam ( the hidden Imam) by Allah. Therefore, it is not possible to make a distinction between what is “religious” and what is “worldly” in the Islamic Republic of Iran which is based on the understanding of velâyat-i fakîh. The fakih, who represents the authority (velayat) of the Twelfth Imam, acts in the name of the hidden Imam and Allah. Hence, the rules he sets regarding the administration of the state and the society is binding not only for the citizens but also for the Shiite ulama who have the freedom to set precedents. In this context, it has even been alleged that obedience to the one who acts as the velâyat-i fakîh is obligatory and disobedience is equal to blasphemy. In a system where the will of the nation has been disregarded with the prevention of the direct election of the veli-yi qakîh by the participation of people, the crisis between the appointed and the elected has ended in favor of those who have been appointed. And the ones elected have been considered legitimate as long as they remained loyal to Khomeini’s path (hatt-ı imâm).
The Source of Authority in the Constitution of the Iranian Islamic Republic Wiıthin the Context of Shia Political Thought